Risk aversion and information aggregation in binary-asset markets - Antonio Filippin; Marco Mantovani (Quantitative Economics, 2023)
We investigate how risk aversion (RA) shapes the informative content of prices in an experimental asset market, where traders are sorted according to their RA. RA should induce steeper individual demands and, under its most common parametrizations, drive equilibrium prices closer to revealing the state. Results support the prediction on individual demands, but not the prediction on prices, which do not vary with RA and are close to the risk-neutral benchmark. This purported conflict is due to traders, particularly the more risk-averse ones, conveying into prices only part of their information.
Keywords: C92; D81; G14; G41; 330; Risk preferences; laboratory experiment; asset markets; information aggregation; Walrasian equilibrium; operational conservatism